Microfinance through innovation - Antonio, Michael G. (The Scholastican Journal, 2016)
The study described the evolution of microfinance in terms of its product line, methodology, outreach and means of ensuring both sustainability and viability. The study outlined the innovations undertaken by microfinanance practitioners in terms of strengthening their respective institutional capabilities to provide better microfinance services that will meet the changing demands of the market. The innovations are also heavily shaped by various reconfigurations in the policy environment and trends set by the international and domestic financial system. In addition, the study provided an account of best practices formulated and adopted by microfinance institutions. It employed the method of desk review of related literature on the innovations of microfinance products and services which are important in enhancing the microfinance institutions' sustainability and responsiveness to their intended clientele. Several key issues pertinent to the innovation were discussed including: access to funding: establishment of partnerships among micro finance institutions with public or private institutions; use of technology for increasing access and provision of micro finance; introduction of new microfinance produts; and the use of non-conventional delivery systems for increasing outreach. Said innovatory approaches and issues were synthesized to generate conclusions in understanding the effects of innovation on institutions and importantly on the clientele.